2022
DOI: 10.3168/jds.2021-20437
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and greater intensity of estrus in recipient lactating dairy cows improve pregnancy per embryo transfer

Abstract: The aim of this study was to determine the association between occurrence and intensity of estrous expression with pregnancy success in recipient lactating dairy cows subjected to embryo transfer (ET). Two observational studies were conducted. Holstein cows were synchronized using the same timed ET protocol, based on estradiol and progesterone in both experiments. At 9 d after the end of the timed ET protocol only animals that had ovulated were implanted with a 7-d embryo [experiment 1 (Exp. 1); n = 1,401 ET e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Alternatively, cows detected in estrus could receive hormonal treatments known to increase fertility. Recently, it has been shown that cows with different estrous intensity, as determined by accelerometer-based automated systems for detection of estrus, have different fertility potential (Tippenhauer et al, 2021;Madureira et al, 2022), and cows with low estrous intensity treated with GnRH at the time of insemination had improved fertility (Burnett et al, 2022). Communication for programming, control, and monitoring is necessary for optimizing functionality and maximizing the value of devices for automating animal management and monitoring tasks (Cross et al, 2004;Berckmans, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, cows detected in estrus could receive hormonal treatments known to increase fertility. Recently, it has been shown that cows with different estrous intensity, as determined by accelerometer-based automated systems for detection of estrus, have different fertility potential (Tippenhauer et al, 2021;Madureira et al, 2022), and cows with low estrous intensity treated with GnRH at the time of insemination had improved fertility (Burnett et al, 2022). Communication for programming, control, and monitoring is necessary for optimizing functionality and maximizing the value of devices for automating animal management and monitoring tasks (Cross et al, 2004;Berckmans, 2017).…”
Section: Discussionmentioning
confidence: 99%